2017
DOI: 10.1016/j.jad.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation and attentional biases in children: An eye-tracking study

Abstract: Background Despite theoretical and empirical evidence for a heighted responsiveness to signals of social-threat in suicidal individuals, no studies to date have examined whether this responsiveness might also manifest in the form of specific biases in attention to interpersonal stimuli. The current study, therefore, examined the presence and nature of attentional biases for facial expressions of emotion in children with and without a history of suicidal ideation (SI). Method Participants were 88 children (44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Another study used the P300 component of event-related potentials (ERPs) during the spatial cueing task found that patients with low rates of suicidal behavior showed difficulty in disengaging attention from suicide-relevant stimuli [40]. Found that children with a history of SI exhibited significantly greater gaze duration toward fearful faces [41]. Investigated the emotional Stroop task (EST) of 820 college students and found that past suicide attempters were slower in responding to the word "suicide", and female past attempters showed more delayed response when their most recent attempt was made in the past 12 months [42].…”
Section: Attentional Biasmentioning
confidence: 99%
“…Another study used the P300 component of event-related potentials (ERPs) during the spatial cueing task found that patients with low rates of suicidal behavior showed difficulty in disengaging attention from suicide-relevant stimuli [40]. Found that children with a history of SI exhibited significantly greater gaze duration toward fearful faces [41]. Investigated the emotional Stroop task (EST) of 820 college students and found that past suicide attempters were slower in responding to the word "suicide", and female past attempters showed more delayed response when their most recent attempt was made in the past 12 months [42].…”
Section: Attentional Biasmentioning
confidence: 99%
“…Only a handful of studies have utilized eye-tracking measures with dot-probe paradigms to examine AB in youth (Burris, Barry-Anwar, & Rivera, 2017; Burris, Barry-Anwar, Sims, et al, 2017; Hilt, Leitzke, & Pollak, 2017; Price et al, 2013, 2016; Tsypes, Owens, & Gibb, 2017). These studies commonly measured (a) initial attention vigilance to emotional faces (e.g., angry face; e.g., Price et al, 2016; Tsypes et al, 2017); and (b) sustained attention preference toward the emotional faces (e.g., Hilt et al, 2017). These indices showed improved internal consistency and reliability compared to RT measures in 9- to 13-year-olds (Price et al, 2015).…”
Section: Multimodal Approaches Facilitate the Delineation Of Attentiomentioning
confidence: 99%
“…These indices showed improved internal consistency and reliability compared to RT measures in 9- to 13-year-olds (Price et al, 2015). Findings from three studies that compared dot-probe eye-tracking and RT indices showed that while eye-tracking measures were associated with levels of rumination (Hilt et al, 2017), suicidal ideation (Tsypes et al, 2017), and transition from anxiety to later depression (Price et al, 2016). Eye-tracking findings were evident even when there were no symptom-related differences in RT scores.…”
Section: Multimodal Approaches Facilitate the Delineation Of Attentiomentioning
confidence: 99%
“…Suicide is one of the complications of a psychiatric disorder and affecting all individuals irrespective of their nation, culture, religion, gender, and class [ 2 ]. Currently, Lithuanians rank first for a suicidal rate, which accounts 31/100k [ 3 ]. Globally, while over 16,000,000 people attempt suicide, and 800,000 commit a suicide every year, other 3000 individuals also commit suicide in a daily base.…”
Section: Introductionmentioning
confidence: 99%